Highly efficient GaN Doherty power amplifier for N78 sub-6 GHz band 5G applications - Al Gburi, Ahmed Jamal Abdullah; Alghamdi, Thamer A. H.; Eid, Mohammed A. Elsayed; Abouelnaga, Tamer G.; Ibrahim, Hamed A.; Hamad, Ehab K. I.; Alathbah, Moath (MDPI AG, 2023)
In this paper, a high-efficiency GaN Doherty power amplifier (DPA) for 5G applications in the N78 sub-6 GHz band is introduced. The theoretical analysis of the matching networks for the peak and carrier transistors is presented, with a focus on the impact of unequal power splitting for both transistors and the recommendation of a post-harmonic suppression network. The proposed design features an unequal Wilkinson power divider at the input and a post-harmonic suppression network at the output, both of which are crucial for achieving high efficiency. The Doherty power amplifier comprises two GaN 10 W HEMTs, measured across the 3.3 GHz to 3.8 GHz band (the N78 band), and the results reveal significant improvements in gain, output power, drain efficiency, and power-added efficiency. Specifically, the proposed design achieved a power gain of over 12 dB and 42 dBm saturated output power. It also achieved a drain efficiency of 80% at saturation and a power-added efficiency of 75.2%. Furthermore, the proposed harmonic suppression network effectively attenuated the harmonics at the output of the amplifier from the second to the fourth order to more than −50 dB, thus enhancing the device’s linearity.